(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the sectors which has gone through a tremendous change in past 25 years. Since the inception of NIFTY IT Index in 1996 with 1000 base value which was later revised to 100 in 2004, the index is currently trading around 25,000 index value approximately. It has gone through the tough times and good times in patches. Despite so many constraints Indian IT Companies has made their mark felt in International arena. It can be due to cheap labor force, highly qualified professionals, government policies for foreign investment, etc. Outsourcing is one big segment which has helped the IT companies to sustain themselves in the competitive environment. In the year 1988, NASSCOM was set up in the financial capital of Mumbai to encourage the growth of IT and ITES in India. Services in hardware, software, networking, training, etc started flourishing in India during this point in time. Companies of developed economy started collaborating with the Indian companies for IT services. The objective for the study is to basically understand the conceptual understanding about the different techniques for predicting the future prices of IT Stocks.